Students’ Perspective on Undergraduate Research Experiences in Indonesian Dental Schools - Erik Idrus; Nieka A. Wahono; Rezon Yanuar; Yuniardini S. Wimardhani; Ria Puspitawati; Lisa R. Amir (International Journal of Dentistry)
Undergraduate (UG) research is considered as an essential part of dental education. Numerous dental schools have included required course-based undergraduate research in their curricula. However, the implementation of UG research courses in the curriculum may vary between dental schools. In the present study, we aimed to evaluate student perspectives on UG research in the curriculum of Indonesian dental schools. A total of 203 participants from 10 dental schools returned the questionnaire. The participants were clinical students of the dentistry profession program who completed their undergraduate dentistry program from 2017 to 2022. The majority of study participants favored UG research in the curriculum of the undergraduate dentistry study program. Less than 20% participants perceived UG research experiments were not important in dental education. Factors that influenced these perceptions included the availability of adequate time to complete the course and sufficient support from research supervisors. Recommendations for improvement included providing an adequate time to complete UG research and adequate supervision to guide students to understand the conceptual background information of the research topics, designs, and scientific communication of data interpretation. Regular monitoring of students’ performance and progress would ensure completion of UG research courses in a timely manner. In conclusion, although UG research as a compulsory course in the Indonesian dental curriculum was well received by the students, overcoming the challenges is essential for the improvement of the research environment for undergraduate dental students.